AVAILABILITY OF CATCHES PRODUCTION WHICH IS LANDED IN FISHERY PORT OF PALABUHANRATU SUKABUMI WEST JAVA - Y Aritonang, Berliana; Yani, Alit Hindri; M Hutauruk, Ronald (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research was conducted in April 2018 at Fishery Port Of Palabuhanratu sukabumi, west java. The purpose of this study is to find out the condition of the catches production that landed on Fishery Port Of Palabuhanratu in 2013-2017. to obtain the projected amount of catches production of skipjack tuna which is landed on Fishery Port Of Palabuhanratu in 2019-2023. The method used in this research is survey method. the highest catches production occurred in 2014 was 10,357,023 Kg and the lowest catches production occurred in 2017 was 3,471,290 Kg. the result of regression analysis the effect of independent variables (ships, fishing gear, and fishermen) to dependent variable (catches production) obtained linier equation Y’ = 4840312+2189,355X1-15738,6X2+2277,168X3.The projection/availability catches production of skipjack tuna shows that the catches production of skipjack tuna in 2019-2023 tends to decrease every year. Decreasing the amount of catches production of skipjack tuna on the projection results is influenced by the trend of the actual data in 2013-2017. the trend obtained for the production per month of skipjack tuna is decreasing during 2013-2017 with the equation y = 33996e-0,013x dan R2 = 0,0777 Keywords : Cathes Production, Skipjack Tuna, Fishery Port Of Palabuhanratu